Teaching and Learning Second Language Listening: Metacognition in Action - Goh, Christine C. M.; Vandergrift, Larry (New York: Routledge, 2022)
This text offers a comprehensive treatment of concepts and knowledge related to teaching second language listening, with a particular emphasis on meta cognition.
Includes Bibliographic references and indexs.
Keywords: Listening-Study and Teaching--Language and Languages-Study and Teaching--Second Languge Acquisition